GAMBARAN KEBIASAAN MENYIKAT GIGI PADA SISWA SDN 4 SANDINGTAMAN KECAMATAN PANJALU KABUPATEN CIAMIS JAWA BARAT (Jurnal Kesehatan Siliwangi, 2021)
Brushing teeth is one of the efforts to prevent tooth decay. The potential for brushing teeth properly and correctly is a factor that is quite important for the maintenance of dental and oral health. The success of maintaining oral and dental health is also influenced by factors such as the use of tools, the method of brushing teeth, as well as the frequency and time of brushing the teeth properly. The results of the Basic Health Research (Riskesdas) in 2018 stated that the proportion of population brushing their teeth every day in West Java reached 96.79%, the correct behavior in brushing teeth only reached 2.89%. While the proportion of people who brush their teeth every day in Ciamis Regency reaches 96.98%, correct behavior in brushing teeth only reaches 2.09%. The purpose of this study was to describe the brushing habits of students at SDN 4 Sandingtaman, Panjalu sub-district, Ciamis district, West Java. This research is a descriptive research, research by observation, namely interviews through the WhatsApp application to determine the habit of brushing teeth in grades one to five. The results showed that the students' brushing technique used was the horizontal technique with a percentage of 42.2%. Frequency of brushing teeth twice a day in the morning after breakfast and at night before going to bed with a percentage of 46.7%. The tooth brushing tool used was a toothbrush according to the criteria for elementary school children with a percentage of 82.2%. Students use toothpaste that contains fluoride with a percentage of 100%. The conclusion is that the students of SDN 4 Sandingtaman have a bad habit of brushing their teeth.